Luz, câmera e likes: o trabalho dos youtubers nas mídias digitais - Denari, Giulianna Bueno (Universidade Federal de São Carlos, 2021)
This thesis aims to comprehend the work processes of content creators for digital platforms, known as YouTubers. The study of digital labor brings forth new possibilities for understanding occupational dynamics and interactions among workers, large companies, and users. Regulations stemming from algorithms, the assignment of responsibilities to workers in managing their time, space, type, and volume of work, complicate the discourses surrounding personal entrepreneurship. YouTube is a digital platform that offers resources for users to create and share video content. For companies, the platform sells advertising space and, primarily, the potential for reach through a massive audience. The central innovation of YouTube lies in the customization of consumed content. Moreover, users themselves not only consume but also create and share content on the platform, enabling deeper identification with their influencers. The guidelines set by the platform dictate the rhythms and work processes, demanding continuous adaptation from YouTubers to ensure the profitability of their endeavors. The work process of YouTubers transcends mere video elaboration and recording; it also involves forming partnerships, bureaucratic management, and the pursuit of expanding their image. With growth in numbers and relevance, YouTubers evolve into a sort of brand, needing to establish connections with other brands through partnerships. The optimistic view of an unpretentious and enjoyable occupation is questioned in the face of exhaustion that arises from the constant pursuit of staying "on top." The research development occurred in two stages and employed a variety of resources. Through online contacts, semi-structured interviews were conducted with YouTubers. Simultaneously, four channels were selected for systematic monitoring of all content produced by and about them. The records were documented in a field notebook, allowing for a reconstruction of their work trajectories. Additionally, secondary quantitative data on income and audience projection were used to comprehend the dynamics outlined by algorithms. The research hypothesizes the fundamental role that YouTubers play in redefining the dynamics of work in digital platforms. YouTubers can be understood as self-entrepreneurs; however, this presumed autonomy is influenced by the actions of the platform's algorithms and the complexity of the digital market. Through this investigation, we aim to examine how YouTubers navigate a landscape marked by dualities and how their practices both shape and are shaped by them. Our research seeks to contribute to a broader understanding of contemporary transformations in the world of work.

Cette thèse vise à comprendre les processus de travail des créateurs de contenu pour les plateformes numériques, connus sous le nom de YouTubers. L'étude du travail numérique ouvre de nouvelles possibilités pour comprendre les dynamiques professionnelles et les interactions entre les travailleurs, les grandes entreprises et les utilisateurs. Les réglementations découlant des algorithmes, l'attribution de responsabilités aux travailleurs dans la gestion de leur temps, de leur espace, de leur type et de leur volume de travail, complexifient les discours entourant l'entrepreneuriat personnel. YouTube est une plateforme numérique qui propose des ressources aux utilisateurs pour créer et partager du contenu vidéo. Pour les entreprises, la plateforme vend de l'espace publicitaire et, principalement, la possibilité d'atteindre un large public. L'innovation centrale de YouTube réside dans la personnalisation du contenu consommé. De plus, les utilisateurs eux-mêmes ne se contentent pas de consommer, mais créent également et partagent du contenu sur la plateforme, permettant une identification plus profonde avec leurs influenceurs. Les lignes directrices fixées par la plateforme dictent les rythmes et les processus de travail, exigeant une adaptation continue des YouTubers pour assurer la rentabilité de leurs initiatives. Le processus de travail des YouTubers transcende la simple élaboration et l'enregistrement de vidéos ; il implique également la formation de partenariats, la gestion bureaucratique et la recherche de l'expansion de leur image. Avec la croissance en termes de chiffres et de pertinence, les YouTubers évoluent en une sorte de marque, ayant besoin d'établir des liens avec d'autres marques grâce à des partenariats. La vision optimiste d'une occupation sans prétention et agréable est remise en question face à l'épuisement qui découle de la poursuite constante de rester "au sommet". Le développement de la recherche s'est déroulé en deux étapes et a fait appel à une variété de ressources. Par le biais de contacts en ligne, des entretiens semi-structurés ont été menés avec des YouTubers. Simultanément, quatre chaînes ont été sélectionnées pour une surveillance systématique de tout le contenu produit par et à leur sujet. Les enregistrements ont été documentés dans un cahier de terrain, permettant une reconstruction de leurs trajectoires professionnelles. De plus, des données quantitatives secondaires sur les revenus et la projection de l'audience ont été utilisées pour comprendre les dynamiques établies par les algorithmes. La recherche émet l'hypothèse du rôle fondamental que jouent les YouTubers dans la redéfinition des dynamiques de travail sur les plateformes numériques. Les YouTubers peuvent être compris comme des autoentrepreneurs; cependant, cette autonomie présumée est influencée par les actions des algorithmes de la plateforme et par la complexité du marché numérique. À travers cette enquête, nous visons à examiner comment les YouTubers naviguent dans un paysage marqué par des dualités et comment leurs pratiques façonnent et sont façonnées par cellesci. Notre recherche vise à contribuer à une compréhension plus large des transformations contemporaines dans le monde du travail.
Light, camera, and likes: the work of youtubers in digital media
Keywords: Trabalho; Plataformas digitais; YouTube; Youtubers; Work; Digital platforms; YouTube; Youtubers; Travail; Plateformes numériques; YouTube; Youtubers; CIENCIAS HUMANAS::SOCIOLOGIA; CIENCIAS HUMANAS